Feasibility of antimicrobial stewardship ward rounds on surgical wards led by a junior pharmacist. (1st August 2022) - Jeffrey, Emma; Duffy, Eamon
Abstract: Background: Antimicrobial stewardship (AMS) is essential to preserve the efficacy of antimicrobials by slowing the development of resistance. AMS ward rounds are a well‐described methodology for optimising and ensuring judicious use of antimicrobials. Pharmacists are valuable members of AMS teams because they possess skills and knowledge that can be used to optimise antimicrobial prescribing. Pharmacists often practice in AMS roles without formal training in this area. Aim: To identify a method which yields the highest number of patients for review, to assess the types of recommendations commonly made, and to assess the rate of uptake of these recommendations, as made by a junior pharmacist. Method: The investigation was carried out at Auckland City Hospital in Grafton, Auckland, New Zealand, over nine weeks between December 2020 and February 2021. Three different methods were utilised for patient identification: automated dispensing reports, pharmacist referral, and random medical record review. Results: Approximately 20 hours were spent and 293 patient records reviewed. Of these, 103 patients had a prescribed antimicrobial which met the criteria for review, 52 recommendations were made, and 35 (67%) of these were actioned by the primary medical team. The medical record review yielded the highest number of patients for review, followed by automated reports, then pharmacist referral. Of the 52 recommendations, the most commonly made recommendation was to stop unnecessary antimicrobials ( n = 26), followed by optimising the dosing regimen ( n = 9), and intravenous‐to‐oral switch ( n = 7). Conclusions: The medical record review identified the highest number of patients for review. The high uptake of recommendations suggests that pharmacists do not need extensive training in AMS to achieve successful outcomes.